Mathematical modelling and numerical simulation of cyclic voltammetry at an electrode covered with an insulating film containing cylindrical micropores - Chevallier, F; Jiang, L; Jones, T; Compton, R (2006)
A general mathematical model for cyclic voltammetry at a planar electrode modified with an insulating surface coating containing non-interconnected cylindrical pores is developed and solved using numerical simulation. Electroactive species are assumed to diffusionally access the electrode only via the pores. The model allows us to explore the effects of different physical and electrochemical parameters on the mass transport properties of such systems and to highlight how they deviate from linear diffusion to a macroelectrode. © 2005 Elsevier B.V. All rights reserved.